For God, mammon, and country : a nineteenth-century Persian merchant, Haj Muhammad Hassan Amin al-Zarb, 1834-1898 /: a nineteenth-century Persian merchant, Haj Muhammad Hassan Amin al-Zarb, 1834-1898. (2018) - Unknown
No abstract available